Gender Perspectives in History Teaching: Challenges and Opportunities - Malazonia, Davit; Pkhaladze, Tamar (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The purpose of this study is to reveal the degree of integration of gender perspectives in the teaching of history in Georgian schools through an analysis of textbooks and teaching practices. Textual material, visual representations, and exercises within textbooks were analyzed to assess gender balance. Semi-structured interviews explored teachers' experiences with teaching gender-sensitive topics, assessed gender representations in textbooks, and evaluated the frequency and effectiveness of using supplementary resources to introduce gender perspectives. Textbook analysis showed that historical narratives are still predominantly male-oriented, especially in political and economic contexts. Women’s roles are mostly confined to family and social spheres, failing to fully reflect their historical contributions. Interviews with teachers revealed a general awareness of the importance of gender perspectives; however, their effective application in practice remains challenging. This is largely due to a lack of appropriate experience and knowledge, indicating a need for professional development programs. Progress towards achieving gender balance in modern history education is a positive trend, though it remains uneven and requires reinforcement. Findings suggest systemic challenges in Georgia’s educational system that hinder the establishment of a balanced gender narrative. A comprehensive approach is needed, involving both content revision of textbooks and professional development of teachers in gender-sensitive teaching methods. This would foster inclusive and critical historical thinking in students, essential for forming a modern, equality-oriented society.